Timing is flipping everything: Is student engagement through the flipped classroom dependent on the year of study it is introduced? A case study in Law - Hewitt, Louise (Compass (Eltham), 2017)
The use of the Flipped Classroom (Bergmann & Sams, 2012, Upchurch, 2013, Flipped Learning Network, 2014) in Higher Education is an exciting development for teaching.  The opportunity offered by the flipped classroom, to adapt the traditional large group lecture and home study elements of a course, can lead to a more effective interactive learning environment. First -hand personal experience has confirmed the pedagogic theory: students engage in the subject matter through actively applying their understanding of the knowledge they have constructed. In the process they often surprise themselves with how much they actually know. Whilst the benefits and challenges posed by this pedagogic approach have been highlighted previously (Simmons and Swan, 2015, Stripe and Carrier, 2015), there remains an unanswered question, could engagement with the flipped classroom be dependent on the year of study it was introduced? It is possible to suggest that it does.